2021
DOI: 10.21273/hortsci16153-21
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and Physiological Responses of Cucumber Seedlings to Different Combinations of Light Intensity and Photoperiod with the Same Daily Light Integral

Abstract: Lighting strategies for morphological and physiological characteristics of horticultural crops often focus on the proper daily light integral (DLI); however, a suitable combination of photosynthetic photon flux density (PPFD) and photoperiod at the same DLI is conducive to optimize the light environment management in vegetable seedling production. In the present study, cucumber seedlings (Cucumis sativus L. cv. Tianjiao No. 5) were grown for 21 days under six different combinations of PPFD and photoperiod at a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…Photoperiod can influence the quantity of light plants experience in a day, the entrainment of their circadian rhythm, and the crucial dark period necessary for flowering in photoperiodically sensitive plants 49 , 50 . Many studies have demonstrated that plants grown under the same DLI and increasing photoperiod at low PPFD resulted in more photosynthetic activity and biomass production 38 , 51 , 52 . Additionally, Arabidopsis 53 (Lepisto et al, 2009) and lettuce 54 were proven to have an increase in their biomass output when exposed to continuous light.…”
Section: Introductionmentioning
confidence: 99%
“…Photoperiod can influence the quantity of light plants experience in a day, the entrainment of their circadian rhythm, and the crucial dark period necessary for flowering in photoperiodically sensitive plants 49 , 50 . Many studies have demonstrated that plants grown under the same DLI and increasing photoperiod at low PPFD resulted in more photosynthetic activity and biomass production 38 , 51 , 52 . Additionally, Arabidopsis 53 (Lepisto et al, 2009) and lettuce 54 were proven to have an increase in their biomass output when exposed to continuous light.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Ji et al [96] found that the increase of photoperiod from 12 to 16 h•day −1 , significantly increased the plant height, stem diameter, and leaf area in three cucumber cultivars. Also, Yan et al [86] observed an increase in cellulose content and improved mechanical strength at transplanting on cucumber plants subjected to a long photoperiod (16 to 20 h•day −1 ). In crops such as watercress, Lam et al [97] found that 20 h•day −1 could Therefore, depending on the species and the objectives to be achieved, the illumination conditions should be optimized, considering that the results obtained in this work had an adequate response between the range of 100 to 300 µmol•m −2 •s −1 for the studied species.…”
Section: Photoperiodmentioning
confidence: 97%
“…When growing plants in VF, the aim is to simulate natural conditions light being one of the limiting resources in this system; therefore, light adaptation has been sought to efficiently optimize light, so studies are conducted with varying levels of intensity to test the effectiveness in different crops to increase the uniformity of leaf reflectance and avoid a lack of light or, on the contrary, light stress. The combined effect of photoperiod and intensity (PPFD) are parameters used to regulate plant growth and quality [85,86]. Low PPDF is associated with decreased plant quality [87].…”
Section: Light Intensitymentioning
confidence: 99%
“…Kwack et al studied the effects of the seedling stage and light intensity on the growth of cucumber grafted seedlings from seed to planting [25]. Yan et al studied the growth response of cucumber varieties to different light environments [26]. Hwang et al studied the effects of photoperiod, light intensity, and temperature on the seedling quality and flower truss of tomato and pepper seedlings [27].…”
Section: Introductionmentioning
confidence: 99%